2020
DOI: 10.3390/molecules25112540
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba Extract Protects against Methotrexate-Induced Hepatotoxicity: A Computational and Pharmacological Approach

Abstract: Ginkgo biloba extract possess several promising biological activities; currently, it is clinically employed in the management of several diseases. This research work aimed to extrapolate the antioxidant and anti-inflammatory effects of Ginkgo biloba (Gb) in methotrexate (MTX)-induced liver toxicity model. These effects were analyzed using different in vivo experimental approaches and by bioinformatics analysis. Male SD rats were grouped as follows: saline; MTX; Gb (pretreated for seven days with 60, 120, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
2
23
0
1
Order By: Relevance
“…The slides were then kept under running water in a glass jar for 10 min and treated with 1% HCl and 1% ammonia water as reported previously. 43 Eosin solution was used afterward for 5-10 min for cytoplasmic staining. After the specified time, slides were rinsed with water and airdried for a short interval.…”
Section: Hematoxylin and Eosin (Hande) Stainingmentioning
confidence: 99%
“…The slides were then kept under running water in a glass jar for 10 min and treated with 1% HCl and 1% ammonia water as reported previously. 43 Eosin solution was used afterward for 5-10 min for cytoplasmic staining. After the specified time, slides were rinsed with water and airdried for a short interval.…”
Section: Hematoxylin and Eosin (Hande) Stainingmentioning
confidence: 99%
“…Several studies have documented the cross-talk between oxidative stress and the inflammation process ( Al Kury et al, 2019 ; Al Kury et al, 2020 ). Therefore, drug therapeutics should be designed to subside the inflammatory process and oxidative distress, by triggering the endogenous antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of COX-2 and iNOS can be prevented by antagonizing p-NFκB expression ( Ali A et al, 2020 ). Natural drug substances have significant anti-inflammatory potential, and we previously showed the inhibitory effect of carveol, polydatin, and Ginkgo biloba on NFkB, COX-2, and iNOS expression in different experimental models ( Al Kury et al, 2019 ; Al Kury et al, 2020 ; Malik et al, 2020 ). We postulated here that carveol reduces hepatocellular necrosis by negatively modulating the expression of mitogen kinase and other inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The exact molecular mechanisms underlying Mtx hepatotoxicity are not clearly understood. Recent studies have indicated that Mtx induced hepatic injury may be due to increasing levels of reactive oxygen species (ROS), hydroxyl radicals and hydrogen peroxide as a result of oxidative injury of the DNA and triggers lipid peroxidation along with decreased levels of antioxidant defense molecules (8,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%